2014
DOI: 10.3109/01658107.2013.856450
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Learning for Rehabilitation in Traumatic Optic Neuropathy

Abstract: Traumatic optic neuropathy is a cause of sudden irreversible visual loss due to optic nerve damage following trauma. Reports of improvement have been noted after observation alone, treatment with corticosteroids, and surgical decompression. However, final visual acuity may not be predictable, with individual patients having little improvement in visual function despite therapy. Perceptual learning improves visual functions by improving the neural processing so as to allow image perception at low signal-to-nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Perceptual learning has been shown to enhance visual function in a variety of ocular disorders presenting with optical blur by increasing the e ciency of neural processing [10][11][12]. The present study describes the effect of perceptual learning on the postoperative visual function after cataract surgery with implantation of a mono-focal intraocular lens.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Perceptual learning has been shown to enhance visual function in a variety of ocular disorders presenting with optical blur by increasing the e ciency of neural processing [10][11][12]. The present study describes the effect of perceptual learning on the postoperative visual function after cataract surgery with implantation of a mono-focal intraocular lens.…”
Section: Discussionmentioning
confidence: 85%
“…However, being a transient phenomenon, adaptation to blur may not be entirely responsible for the bene cial effect on a long term. The enhancement of neural sensitivity so as to enable image processing at low signalnoise ratios has been proposed and may account for the improvement following perceptual learning [11,12]. Blur detection and discrimination of single blurred edges have been demonstrated to be contrast detection tasks [14] and improvement of contrast detection through perceptual learning may enhance the processing of blurred images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only five participants were included in the study. Concerning optic neuropathy, to the best of our knowledge, one study only, a case report, reported the beneficial effect of visual perceptual learning (Vaitheeswaran et al, 2014). Interestingly, another study reported an improvement in feature search performance after PL in patients with AMD, glaucoma and RP (Liu et al, 2007).…”
Section: Pre-chiasmatic Disorders and Perceptual Learningmentioning
confidence: 85%
“…To overcome the issue in adults, neuroplasticity, and perceptual learning has been shown to enhance visual function by increasing the efficiency of neural processing, which has also been studied in a variety of ophthalmic disorders, such as optic neuropathy. [35][36][37] Although amblyopia and glaucoma are not the same disease entity, the fundamental idea behind the concept of those disease entities potentially gives a new aspect in eyes with intereye asymmetric glaucoma. Therefore, further studies evaluating the nonocular site implicated in intereye asymmetry are needed.…”
Section: Discussionmentioning
confidence: 99%